2013
DOI: 10.1186/1746-1596-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HE4 estimation in comparison with CA125 in diagnosis of ovarian cancer and assessment of treatment response

Abstract: BackgroundHuman epididymis protein 4 (HE4) is a novel and specific biomarker for ovarian cancer. The aim of this study is to evaluate a new tumor marker, HE4, in comparison with CA125 in diagnosis of epithelial ovarian cancer (EOC) and benign gynecological diseases.MethodsCA125 and HE4 serum levels were determined in 30 patients with epithelial ovarian cancer (21 serous, 6 endometrioid and 3 mucinous tumors), 20 patients with benign gynecological diseases (8 patients with ovarian cyst, 5 patients with endometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 41 publications
10
48
2
2
Order By: Relevance
“…In the present study, the CA 125 showed the same sensitivity of HE4 (92%), this result is consistent with the study by Karlsen et al (2012) However, this shows consistency with previous studies, as the study by Fujiwara et al (2015), who found that the AUCs for HE4 were better than the AUC for CA 125 in distinguishing between benign diseases and EOC, the study by Hamed et al (2013) AUC values were (0.96) for HE4 and (0.82) for (CA 125), the study by Karlsen et al (2012) AUC was highest for RMI (0.905) followed by HE4 (0.864) and CA125 (0.854), respectively and for the Montagnana et al (2009) study, AUC for HE4 is higher than CA 125. There was a highly significance (r = 0.746, p<0.001) correlation between levels of CA 125 and tissue HE4 measured by real time PCR in all groups of the study.…”
Section: Int J Cancersupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, the CA 125 showed the same sensitivity of HE4 (92%), this result is consistent with the study by Karlsen et al (2012) However, this shows consistency with previous studies, as the study by Fujiwara et al (2015), who found that the AUCs for HE4 were better than the AUC for CA 125 in distinguishing between benign diseases and EOC, the study by Hamed et al (2013) AUC values were (0.96) for HE4 and (0.82) for (CA 125), the study by Karlsen et al (2012) AUC was highest for RMI (0.905) followed by HE4 (0.864) and CA125 (0.854), respectively and for the Montagnana et al (2009) study, AUC for HE4 is higher than CA 125. There was a highly significance (r = 0.746, p<0.001) correlation between levels of CA 125 and tissue HE4 measured by real time PCR in all groups of the study.…”
Section: Int J Cancersupporting
confidence: 83%
“…There was a highly significance (r = 0.746, p<0.001) correlation between levels of CA 125 and tissue HE4 measured by real time PCR in all groups of the study. In study by Hamed et al (2013) a positive correlation between serum levels of HE4 and CA 125 was observed in women with epithelial ovarian cancer, benign gynaecological disease group and control group (r = 0.5, p<0.01) which was consistent with the present study results.…”
Section: Int J Cancersupporting
confidence: 82%
“…However, serum HE4 levels rarely increased in benign gynecologic conditions, suggesting its complementary role to CA125 [13][14][15] . Similar to CA125, HE4 levels were significantly higher in patients with ovarian cancer compared with levels observed in patients with benign disease or healthy controls 16 .…”
Section: Resultsmentioning
confidence: 65%
“…Confirmation of this HE4 behaviour in a larger number of patients is therefore required. The suggestion that HE4 is a good indicator for the remission from the disease was reported by a follow up study by Hamed et al 18 in which it was shown that the values of HE4 correlated with the clinical response to treatment or remission from the disease, as documented by CT imaging.…”
Section: 11mentioning
confidence: 85%